Numerical simulation model for short circuit prediction under compression and bending of 18650 cylindrical lithium-ion battery. (October 2018) - Sheikh, Muhammad; Rehman, Sheikh; Elkady, Mustafa
Abstract: Lithium-ion batteries are considered efficient energy source for current electric vehicles (EVs) due to better power and energy densities; however, safety of these batteries is vital when it comes to large scale deployment. Short circuit of batteries is one of the concern as it can spread quickly within battery module or pack if not controlled at cell level. In this paper single lithium-ion battery cell is investigated where two mechanical abuse conditions, compression and bending are used to investigate short circuit and propagation of failures due to short circuit. Quasi-static loading approach is used for mechanical abuse conditions. Numerical simulation tool LS-DYNA is used to model battery cell where each layer thickness is considered 0.3mm and concentric layered formation is used for this purpose. Separator failures are analysed using simulation models, where at maximum displacement separator temperature increases significantly and drop in force is observed, another significant finding from separator layer analysis is the high-temperature locations. In the case of three-point bend test which has immediate short circuit response and circular punch test where a slow build-up of short circuit is evident from experiment, separator failure occurs well in advance for short circuit.